The spectacle sensor / Muhammad Nur Ikhwan Mohd Zain … [et al.] - Mohd Zain, Muhammad Nur Ikhwan; Abu Bakar, Aleesa Atiqa; Mazlan, Nur Fatin Hazwani; Salehan, Sahira Faqihah; Ibrahim, Muhammad Nor Irfan; Wei Loon, Koe (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
To enhance accessibility and independence for the visually impaired, our group is developing a spec sensor—a revolutionary device designed to provide real-time environmental information and sensory feedback. The spec sensor goes beyond traditional aids by offering a comprehensive suite of features tailored to the daily needs of the blind community. This device aims to identify and announce nearby objects, from furniture to specific items on grocery shelves, enabling users to navigate and interact with their surroundings more confidently. Additionally, the sensor offers color recognition capabilities, describing the colors of clothing or natural elements like flowers, thereby enriching the user's sensory experience. Moreover, the spec sensor enhances environmental awareness by alerting users to potential hazards such as uneven surfaces or changes in lighting conditions.